Gender Stereotype in Indonesian Movies: The Representation of Gender Stereotype in “Lovely Man” (2011) (EUFONI: Journal of Language, Literary, and Cultural Studies, 2025)
This study explores the representation of gender stereotypes and the experiences of transgender individuals in the Indonesian film Lovely Man (2011), directed by Teddy Soeriaatmadja. Using a qualitative narrative analysis, the research examines how the film portrays societal norms, discrimination, and personal identity through the relationship between Syaiful, a transgender woman, and her daughter, Cahaya. Guided by Judith Butler’s (1990) theory of gender performativity and Michel Foucault’s (1978) discourse on power, the analysis reveals how the film challenges traditional gender expectations and critiques systemic marginalization. Through visual, narrative, and dialogic elements, Lovely Man exposes the emotional and social toll of stereotyping while affirming the resilience and humanity of marginalized individuals. The film’s nuanced portrayal of gender identity and familial acceptance fosters empathy and encourages viewers to question societal biases. Although the study is limited to a single film, it highlights the transformative potential of cinema in addressing gender-based discrimination. The findings suggest that Indonesian cinema can play a vital role in promoting inclusive narratives and reshaping cultural understandings of gender and identity.